A prospective study of maternal outcome of labor and perinatal outcome in premature rupture of membranes - Andrabi, Syed Uzma; Khan, Ishtiyaq Ahmad; Bashir, Nadia; Nisa, Zeenat U. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Premature rupture of membranes refers to rupture of fetal membranes prior to the onset of labor. PROM is of two types viz. term PROM and preterm PROM. The incidence of PROM is at an average of 10%. In 70% of the cases, it occurs in pregnancies at term. Preterm PROM- defined as PROM prior to 37 weeks of gestation- complicates 2% to 4% of all singleton and 7% to 20% of twin pregnancies. It is the leading identifiable cause of premature birth and accounts for approximately 18% to 20% of perinatal deaths. Methods: This study was conducted in the tertiary care teaching institute in the state of Jammu and Kashmir, India. After taking an informed consent, a proforma was filled on subject history, examination and investigations. These subjects were followed until delivery and then neonates were also followed. Results: Incidence of PROM was 8.76% of which 54.7% were primigravida and 45.3% were multigravida. Most of the patients (70.4%) were term, only 29.6% were preterm with gestational age of <37 weeks. Incidence of PPH was 2.8%, puerperal pyrexia occurred in 9.8%. The incidence of RDS in neonates was 8.9% while the incidence of neonatal sepsis was 6.7%. There was 1.1% perinatal mortality. Conclusions: From this study it can be concluded that basic aim of obstetrician should be to identify the risk factors leading to PROM, to treat complications and implement strict aseptic precautions to prevent maternal and neonatal morbidity.